Effects of appliying mixed biofertilizer on changes in chlorophyll-a concentrations in media that given peat soils - Joel Rikardo Sinaga; Syafriadiman Syafriadiman; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis research was conducted from October to November 2019 at the peatland of Kualu Nenas Village, Tambang, Kampar District, Riau Province. The purpose of this research is to get ‘ The effect of applying mixed biofertilizer on changes in chlorophyll-a concentration in media that were given peat soils’ The method used in this study was the experimental method of using the Complete Random Design (CRD), 1 factor with 6 treatment levels and 3 replications. The treatment used is P0 (without biological fertilizers), P1 (provision of biological fertilizer 100%), P2 (provision of biofertilizer mixture 25% human waste : 75% cow manure biofertilizer), P3 (provision of biofertilizer mixture 50% human waste : 50% cow manure biofertilizer), P4 (provision of biofertilizer mixture 75% human waste : 25% cow manure biofertilizer), P5 (the provision of biofertilizer 100% human waste). The study was conducted for 30days. The results of this research showed a mixture of biofertilizer 75% human waste : 25% cow manure biofertilizer provides the best solution on chlorophyll concentration, which is 0,037mg/L and highest concentration occurred on day 20. The water quality parameters analyzed during the research were optimal for changed in chlorophyll concentration with a water temperature of 27-29 oC, pH 5-7, DO 3,8-6,7 ppm, Nitrate 4,75 mg/L and Orthoposfat 3,50 mg/L.  Keywords: Peat Soil, Formulation Biofertilizer,Chlorophyll.